Unleashing the Potentials: Nurturing Students’ 4Cs Skills through Project-Based Learning with ICT in EFL Classrooms - Waly, Muchamad Muchibbuddin; Ashadi, Ashadi (Universitas Muhammadiyah Yogyakarta, 2024)
Project-based learning (PjBL) integrated with information and communication technology (ICT) has emerged as a promising learning model to nurture students' 4Cs skills (critical thinking, communication, collaboration, and creativity) in the EFL classroom. Therefore, this study aims to explore the perceived benefits and challenges of integrating PjBL with ICT in nurturing students' 4Cs skills in EFL classrooms. The research employed a qualitative single case study design involving semi-structured interviews with four EFL teachers and focus group discussions with twelve students. Thematic analysis was conducted on the collected data to identify emerging themes and patterns. The findings revealed several perceived benefits, including improved oral and written communication abilities, enhanced individual and group collaboration, clearly defined and implemented problems and solutions, and fostered creative idea generation, selection, and presentation. However, challenges such as time management issues, technical problems, physical and psychological burdens, and lack of sufficient teacher training and scaffolding were also identified. The study suggests that integrating PjBL with ICT can nurture the 4Cs skills essential for success in the 21st century. However, effective implementation necessitates resolving the highlighted issues, which include adequate teacher training, resource allocation, and support mechanisms. The implications of the research extend beyond the EFL classroom, showing the potential of this pedagogical model to cultivate crucial 21st-century skills across diverse educational contexts.